If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2+12=76
We move all terms to the left:
x2+12-(76)=0
We add all the numbers together, and all the variables
x^2-64=0
a = 1; b = 0; c = -64;
Δ = b2-4ac
Δ = 02-4·1·(-64)
Δ = 256
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{256}=16$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-16}{2*1}=\frac{-16}{2} =-8 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+16}{2*1}=\frac{16}{2} =8 $
| 5+30x+10-5x=16x+25-4 | | 5(x+1)=6x-3+x | | t/4-2=16t= | | 1+6x/4+1/2-x/4=4x+7/5-2/10 | | a/6+1=16a= | | x+1,28=5,9 | | 9m+10=100m= | | 5m-15=8m | | 6(x-3)-(x+4)=4 | | 5y-11=34y= | | 3(6x+3)-5(3x-4)=5+2(x+3) | | 8.75x+7=24.5 | | 4(x–7)=x+20 | | 9x+(x-7)=3(5x-4)-(11-3x) | | 2y-17=7-6y | | 6(x-3)-(x-4)=4 | | 3x-1/2+x+5/3=3x+9/4 | | 3(6x+2)-5(3x-4)=7+2(x+5) | | x-5(x-3)=5x-3 | | 30-2x=x+15 | | 3x–8=12–x | | 8×-12=-5x+12 | | 8y÷6=4y-1 | | 0.5^x=0.6 | | 21+x=2@ | | 6(f+5)−=(f−6) | | 13d+3=7d+51 | | 5(5g+2)/4=40 | | 24.6=4c-9 | | 11d+7=5d+19 | | 8e-7=29 | | 14x^2-37x+42=0 |